TISSUE FLOW AND BIOMASS PRODUCTION OF PIATÃ GRASS IN FUNCTION OF DEFOLIATION FREQUENCY AND NITROGEN FERTILIZATION (Colloquium Agrariae. ISSN: 1809-8215, 2019)
Due to the multifactorial interplay of the morphogenic, morphologic and agronomic characteristics of forage species, it is necessary to find management options that increase the production and utilization of the forage mass of grasses when submitted to different defoliation frequencies and nitrogen application levels The objective of this study was to assess the effects of two defoliation frequencies and two nitrogen levels applied in a single dose on the morphogenic and structural characteristics and forage production of Piatã grass (Brachiaria brizantha cv. Piatã) grown in the rainy season. The experiment was carried out in the agrostological field of the School of Veterinary Medicine and Zootechnics of Mato Grosso do Sul Federal University (UFMS), in Campo Grande, Mato Grosso do Sul, Brazil. The experimental area was composed of 12 plots measuring 18 m² each, planted with Brachiaria brizantha cv. Piatã (Syn. Urochloa brizantha cv. Piatã). The experimental design was completely randomized and the treatments consisted of two defoliation frequencies (with cutting intervals of 28 and 35 days) and two nitrogen levels (100 and 200 kg ha-1 of N, in the form of urea, in a single application ), with three repetitions per treatment. The results showed that for Piatã grass swards established in soil having good fertility, the recommended management strategy is to set the minimum cutting or grazing height at 20 cm, with an interval of 28 days when the grass reaches an approximate height of 30 cm. In swards established in the rainy season, to reduce the fractioning of the N dose, it should be applied in a single dose of up to 100 kg of N ha-1 immediately after the first cutting.